In-Situ Synthesis and Characterization of Biodegradable Estolides via Epoxidation from Canola Biodiesel - Venu Babu Borugadda; Ajay K. Dalai (Lubricants, 2018)
Research on the formulation of estolides from plant seed oils has attracted substantial attention due to their favorable low-temperature properties and environmentally friendly nature. The present research investigates the formulation of canola biodiesel derived estolides for low-temperature applications. The dual-step research method includes ring opening of epoxidized canola biodiesel in the presence of oleic acid, followed by esterification with oleic acid to produce estolides using a mesoporous aluminosilicates possessing Modernite Framework Inverted (MFI) type pentasil structure as a heterogeneous acidic catalyst. Prepared catalyst was characterized to measure the properties essential for the effective catalysis. The catalyst demonstrated promising activity for the estolides formation, >95% conversion was achieved at 110 °C for 6 h using 15 wt % of catalyst loading. 1H NMR technique and oxirane oxygen titrimetric analysis were employed to determine product purity. Physicochemical properties of the reaction products were determined by standard methods and characterization results revealed that the formulated estolides had improved low-temperature, lubricity and rheological properties, and thermo-oxidative stability. Also, biodegradability of the estolides was found to be 92% within 28 days as per the bio-kinetic model. Wear scar diameter of 106 µm was noticed for 10% of alkoxide blend with standard diesel fuel. Overall, outcomes of the physicochemical characterization data indicated that the prepared estolides can act as possible alternative bio-lubricant basestock for various low-temperature applications.